LA FILOSOFÍA DE LA ADMINISTRACIÓN DE PETER DRUCKER - Puell Palacios, Juan (2009)
In Peter Drucker’s philosophy on the organizations he thinks widely concerning money, as a vital resource for the business, is like the deep thought for the philosophers. It is advisable to work with foreign money, but the same time the commitment must honor to return it and this way to be able to be a credit subject on the financial market. An approach does on the management in the organizations, the same one that, according to his concept it belongs related to the people who has responsibility of taking them to the success. Here Peter Drucker establishes a relation unbreakable between the business and the client. Customer’s satisfaction depends on the changes that the management could make to yours favor and this way support it with loyalty and conviction. When Peter Dancker analyzes the knowledge he considers it to be a link between learning and education to make it more productive when it is applied. He thinks that the today knowledge is obsolete for tomorrow for the dynamics of the scientific and technological changes. Finally he considers the persons, recognizing theirs fortresses, potentials and proposes that the organizations should invest in the development of theirs capacities, skills and human qualities. All the managers must confront the challenge of creating our own philosophy in order that the managerial organizations apply the knowledge for the well-being of the throughout society.